Relationships between affective characteristics factors, family upbringing factors, violence influence factors, and bullying behavior of Islamic private schools students’ in Songkhla province - และหีม เกษตรชัย; สังขรัตน์ อุทิศ (Journal of Liberal Arts Prince of Songkla University, 2016)
The objective of this research was to determine the relationships between affective characteristic factors, family upbringing factors, violence influence factors, and bullying behavior of Islamic private schools students’ in Songkhla province. The data were collected by interviewing 1,950 students, and using R program in analyzing frequency, percentage, mean, standard deviation, and Pearson product moment correlation coefficient. It was found that frustration, strict upbringing, liberal upbringing, permissive upbringing, influences of peer violence, television violence, game violence, and parental violence held the positive relations to students’ bullying behavior statistically significant at 0.001 level. Clearly, the frustration and the influence of parental violence were the most strongly related to students’ bullying behavior.